O enigma do desejo no assassinato – uma análise crítica da psicologia criminal - Usevicius, André Alvares (2023)
This research performs a critical analysis about Criminal Psychology, through the mapping of desire regarding the perpetration of mass murders executed by young brazilians. To this end, the researcher uses the experimentation of a research method coined as “cartographic essay”, guided by the philosophy of difference and epistemological anarchism. By critically and historically analyzing the creation of assassination and the knowledge that supports it – the Criminology and the Criminal Psychology that supports it –, we intend to problematize the etiological logic that creates generic and reductionist criminal models. Therefore, as a way of highlighting this problem, this research redeem the relationship between desire and murder, analyzing the complex and unique criminal phenomenon that crosses the category of mass murder, highlighting how the desire of young people captured by this discourse operates – something that can be demonstrated by the study of a case accomplished at the end of the work, marked by singularity and contradiction.